2019
DOI: 10.1177/1534734619859214
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and Repair of Skin Wounds: Various Strategies for Treatment

Abstract: Skin as a mechanical barrier between the inner and outer environment of our body protects us against infection and electrolyte loss. This organ consists of 3 layers: the epidermis, dermis, and hypodermis. Any disruption in the integrity of skin leads to the formation of wounds, which are divided into 2 main categories: acute wounds and chronic wounds. Generally, acute wounds heal relatively faster. In contrast to acute wounds, closure of chronic wounds is delayed by 3 months after the initial insult. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 205 publications
(303 reference statements)
0
67
0
Order By: Relevance
“…Though their clinical potential has been favorably evidenced, there are some challenges to consider with the use of ADSCs. This cell population is not immortal and displays signs of aging and loss of chemokine markers with repeat culturing[ 50 ]. Further, adipose tissue can widely vary in its metabolic activity and capacity for proliferation and differentiation depending on the site of tissue harvest and patient characteristics, such as age and sex[ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Though their clinical potential has been favorably evidenced, there are some challenges to consider with the use of ADSCs. This cell population is not immortal and displays signs of aging and loss of chemokine markers with repeat culturing[ 50 ]. Further, adipose tissue can widely vary in its metabolic activity and capacity for proliferation and differentiation depending on the site of tissue harvest and patient characteristics, such as age and sex[ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Marfia et al[ 45 ] identified that autologous ADSCs have an altered genotype in diabetic patients, which is characterized by decreased potency and expression of vascular endothelial growth factor-A (VEGF-A) and chemokine receptor CXCR4. Judicious use of ADSC therapy requires close patient surveillance for tumor formation as well as consideration of strategies to improve cell homing and transplantation[ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of strategies have been explored to improve chronic wound outcomes. Tissue engineering approaches, such as the use of stem cells, modulating the immune response, and the use of scaffolds, cell therapies or growth factors are widely reported ( Rezaie et al, 2019 ). Evidence based decision systems have also been developed to progress from decision based support systems ( Schaarup et al, 2018 ) and a large field of research is devoted to the point of care monitoring and analysis of chronic wounds ( Sheets et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%